Fireboat the heroic adventures of the John J. Harvey - Kalman, Maira 1949- (G.P. Putnam's Sons, 2002)
A fireboat, launched in 1931, is retired after many years of fighting fires along the Hudson River, but is saved from being scrapped and then called into service again on September 11, 2001
Hier auch später erschienene, unveränderte Neuaufl. / Nachdrucke
Keywords: John J. Harvey (Fireboat) -- Juvenile literature; World Trade Center (New York, N.Y.) -- Juvenile literature; John J. Harvey (Fireboat); World Trade Center (New York, N.Y.); World Trade Center -- New York, NY; Geschichte 1931-2001; September 11 Terrorist Attacks, 2001 -- Juvenile literature; Boats and boating; Fire extinction; September 11 Terrorist Attacks, 2001; Feuerlöschboot; Elfter September; USA; Hudson River; Sachbilderbuch